Changing from Clinician-Collected to Self-Collected Throat Swabs for Oropharyngeal Gonorrhea and Chlamydia Screening among Men Who Have Sex with Men - Chow, Eric P. F. (J Clin Microbiol, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has led many clinics to move from clinician-collected to self-collected oropharyngeal swabs for the detection of sexually transmitted infections (STIs). Before this change, however, self-collection was used primarily for genital and anorectal infections, with only limited studies on the performance of self-collection of oropharyngeal swabs for oropharyngeal STI detection. The Melbourne Sexual Health Centre (MSHC) changed from clinician-collected to self-collected oropharyngeal swabs for oropharyngeal gonorrhea and chlamydia screening on 16 March 2020 in order to reduce health care worker risk during the COVID-19 pandemic. We compared the proportions of valid and positive samples for gonorrhea and chlamydia among men who have sex with men (MSM) in two time periods; the clinician collection period, between 20 January and 15 March 2020, and the self-collection period, between 16 March and 8 May 2020. A total of 4,097 oropharyngeal swabs were included. The proportion of oropharyngeal swabs with equivocal or invalid results for Neisseria gonorrhoeae was higher in the self-collection period (1.6% [24/1,497]) than in the clinician collection period (0.9% [23/2,600]) (P = 0.038), but the proportions did not differ for the detection of Chlamydia trachomatis. The positivity rates of oropharyngeal N. gonorrhoeae (adjusted prevalence ratio [PR], 1.07 [95% confidence interval CI, 0.85 to 1.34]) (P = 0.583) and oropharyngeal C. trachomatis (adjusted PR, 0.84 [95% CI, 0.51 to 1.39]) (P = 0.504) specimens did not differ between the two periods. Self-collected oropharyngeal swabs for the detection of N. gonorrhoeae and C. trachomatis have acceptable performance characteristics and, importantly, reduce health care worker exposure to respiratory infections.